L’exploitation des tice au service de l’enseignement des langues à objectif spécifique - Gajewska, Elżbieta; Sowa, Magdalena (Studia Romanica Posnaniensia, 2014)
The so-called latest technologies in the world of today constitute an indispensable component of teaching or learning foreign languages. Given as an obvious element of social life, they are regarded by teachers as effi cient tools for acquiring and perfecting various skills, such as communicative ones. The dynamic development of the multimedia, also in the area of language teaching, incessantly faces language teachers with new challenges, whose aim is to fully utilise the potential of the latest technologies in the process of language teaching that respects learners’ individual needs. The aim of this article is to present possible ways of using the multimedia, helpful in drawing language lesson plans for vocational language groups. The article deals with the area of communication and information technologies used in the classroom as these have recently undergone changes. Also, a discussion is presented of the advantages and disadvantages of the latest multimedia used in the didactic process. The article also seeks to answer the question how much the latest technologies cater for the needs of specialist glottodidactics.